Utilization of Bitumen, Aggregate and Wax with Rubber Tyre in a Flexible Pavement. Issue 1 (November 2021) - Mohan, Rajat; Gupta, Aakash; Gaur, Kshitij
Abstract: With continuous wear and tear actions of rubber tyre on roads, a pile of waste rubber gets accumulated every year and it is posing severe threats to the environment. Due to high temperature in the summers, the road tends to become brittle, which may cause separation of binder in the bituminous road causing heavy cracks, so usage of wax tends to reduce the formation of cracks and improve the flexibility of road. This study aims to examine the effects on properties of the bitumen-aggregate mixture when the aggregates are partially replaced by similar sizes of waste rubber tyre particles and bitumen in the mix are partially replaced by a crumb waste rubber tyre, with partial addition of wax content in the bituminous samples. For this purpose of testing the suitability of using rubber waste in road pavement, Marshall Stability test is conducted on several bituminous mixtures. Varying percentages of rubber tyre, such as 0%, 5%, 10% and 15%, are used with different percentages of bitumen content (4.0, 4.2, 4.4, and 4.6), and varying percentages of paraffin wax (0-5%) is also added in the specimen with rubber and bitumen. This is utilized in obtaining the optimum content of bitumen required for best suitability of flexible pavement as well as to assess the durability and strength of a pavement. This study is performed on various mixtures, for the values of bulk density, air voids, stability value and flow value. The studies show that bitumen content corresponding to the maximum stability value and maximum bulk specific gravity in bituminous mixture, indicating the optimum bitumen percentage that can be replaced with crumb rubber tyre. This paper discusses the partial replacement of both aggregate and bitumen in the bituminous mixture, containing some percentages of paraffin, which can help in improving the serviceability level and assists in enhancing the flexibility and cohesion of road to resist heavy loadings of vehicle.